외팔보 실험 및 유한요소해석을 이용한 AISI 316L 스테인리스 강의 L-DED 적층제조 시 공정변수에 따른 잔류응력 형성거동 분석 - 정종욱; Jongwook Jung; 하경식; Kyeongsik Ha; 이욱진; Wookjin Lee (대한금속·재료학회지, 63(10), 2025)
Laser directed energy deposition (L-DED) is a metal additive manufacturing technique that provides high design flexibility and enables the fabrication of complex geometries. However, the rapid and localized thermal cycles inherent to the process lead to the formation of residual stresses, which degrade mechanical properties and dimensional accuracy of the fabricated parts. In this study, the effect of L-DED process parameters on residual stress formation was investigated using AISI 316L powder. Experiments were conducted by depositing material onto substrates fixed at both ends, and bending deformation after constraint removal was measured to evaluate the residual stress. The influences of key process parameters, including laser power, scan speed, and scanning strategy, were systematically examined. A finite element method (FEM) simulation based on the birth and death technique was developed to replicate the thermal and mechanical behavior during the L-DED process. The simulation incorporated the temperature gradient mechanism (TGM) and thermal strain of deposited layers to improve prediction accuracy. The FEM model successfully reproduced the experimental trends, accurately predicting both the bending height and residual stress distributions under various processing conditions. In particular, the model effectively captured the influence of different scanning strategies on the stress profile, demonstrating its ability to simulate processinduced thermal and mechanical behaviors with high fidelity. These findings provide a quantitative basis for optimizing L-DED parameters and contribute to process design strategies aimed at minimizing residual stress and enhancing dimensional stability in metal additive manufacturing. (Received 30 June, 2025; Accepted 1 August, 2025)